2009
DOI: 10.1179/174328109x463020
|View full text |Cite
|
Sign up to set email alerts
|

Metallic iron whisker formation and growth during iron oxide reduction: basicity effect

Abstract: The effect of basicity on the metallic iron whisker growth during wü stite reduction was studied in the present investigation. Compacts of pure and CaO/SiO 2 doped wü stite were synthesised. The annealed compacts were isothermally reduced in thermogravimetric apparatus with CO gas at 800-1100uC. The course of reduction was followed by measuring the weight loss as a function of time. X-ray diffraction (XRD), scanning electron microscope (SEM), optical microscope and porosity measurements were used to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Abdel Halim et al investigated the formation of metallic iron whiskers during wüstite reduction with CO. Reduction at 800 °C leads to a low reduction rate and 40% conversion.…”
Section: Rate‐limiting Mechanism During Iron Oxide Reductionmentioning
confidence: 99%
“…Abdel Halim et al investigated the formation of metallic iron whiskers during wüstite reduction with CO. Reduction at 800 °C leads to a low reduction rate and 40% conversion.…”
Section: Rate‐limiting Mechanism During Iron Oxide Reductionmentioning
confidence: 99%
“…Reduction swelling of iron oxide pellets or compacts has been studied by a number of investigators 1–26. The formation and growth of fibrous iron whiskers during the reduction of wustite to iron has been determined to be the major cause for catastrophic swelling.…”
Section: Introductionmentioning
confidence: 99%
“…The formation and growth of fibrous iron whiskers during the reduction of wustite to iron has been determined to be the major cause for catastrophic swelling. It has been found that other oxides in the pellet6–19 and firing and reduction conditions20–25 have significant effects on iron whisker formation and growth. Industrial ironmaking processes are carried out with various mixtures of CO, CO 2 , H 2 , H 2 O, and N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Seaton et al [36] referred to swelling indices between 20 and 27% as acceptable and normal. Also, Nascimento et al [37] and Abdel Halim et al [38] proposed that swelling indices around 20% are normal, whereas much higher values are considered catastrophic. These much higher indices were exemplified by studies reporting swelling indices exceeding 400% [38].…”
Section: Tumble Index and Swellingmentioning
confidence: 99%
“…Also, Nascimento et al [37] and Abdel Halim et al [38] proposed that swelling indices around 20% are normal, whereas much higher values are considered catastrophic. These much higher indices were exemplified by studies reporting swelling indices exceeding 400% [38]. In contrast to these values, the higher swelling indices during reduction accompanied by the addition of upgraded BF sludge in the present study were modest.…”
Section: Tumble Index and Swellingmentioning
confidence: 99%